Influence of immortelle (Helichrysum italicum (Roth) G. Don) and lavender (Lavandula angustifolia Mill.) hydrolates on oxidative stress and antioxidative parameters in human serum - Krgović, Nemanja; Miljak Vujičić, Gordana; Kukić Marković, Jelena; Simić, Milena; Miljak, Mijo; Kotur Stevuljević, Jelena (Archives of Pharmacy, 2025)
A number of studies suggest that different antioxidants play important roles in the body's antioxidant defense system. Hydrolates, by-products of essential oils, commonly obtained by steam distillation, are recognized to possess remarkable pharmacological activities, in particular an antioxidant activity. This study aimed to investigate and compare the antioxidant properties of immortelle hydrolate (IH) and lavender hydrolate (LH) using an ex vivo platform, i.e. human serum. To assess their impact on oxidative stress / antioxidative parameters, spectrophotometric biochemical assays were applied. The GC/MS analysis revealed that the main constituents were italidione I (17.2%), linalool (15.6%), a-terpineol (13.7%), terpinen-4-ol (6.3%) and nerol (5.2%) in IH, and linalool (19.6%), terpinen-4-ol (17.0%), a-terpineol (13.6%) and borneol (5.8%) in LH. The results showed that serum samples with LH, along with tert-butyl hydroperoxide as a pro-oxidant, had lower concentrations of the TOP (total oxidant potency) parameter, and slightly higher concentrations of the TAC (total antioxidant capacity) and SHG (total sulfhydryl groups) parameters compared to IH samples. Moreover, a significant difference in the OSI (oxidative stress index) parameter was observed (IH vs. LH – 49 (41–58) vs. 70 (61–75), p
Keywords: hydrolates; human serum; oxidative stress; antioxidant activity